READING AND ELABORATING LITERARY WORK IN BUILDING GOOD CHARACTERS - Kusumayanthi, Susie (English Education Department of STKIP Pasundan, 2020)
Certain disciplines such as civic education and religious education are thought to be able to develop human capital in accordance with character building, while other disciplines - among others English language education- could not be able to fulfill the needs to promote it. In this study, the researcher aims to find out whether or not English language education can help building good characters. In seeking for the answer, as many as one hundred participants from a university were given activities to read and elaborate literary works as one of the efforts that language teachers may do in building good characters from their classes. The method used in this research is descriptive method by collecting, processing, analyzing, interpreting, and concluding data. The data were gathered based on the theory guiding of the reader response, known as The Reader’s Response Strategy, and a questionnaire from six pillars of the establishment of the character, as well as collected through interview.